FACTORS AFFECTING LISTENING ANXIETY OF SENIOR HIGH SCHOOL STUDENTS IN ENGLISH CLASSROOM - Khairani Ade Guswita; Sugirin Sugirin (Universitas Bengkulu, 2021)
In the process of listening, anxiety is a natural response that occurs to students who can divert the listening process. Thus, the purpose of this study is to find out factors affecting listening anxiety of senior high school students in the English classroom. The method used in this study was mixed method because the data obtained were in the form of qualitative and quantitative data. Participants in this study were 35 senior high school students in 2019-2020 academic year. The instrument used to collect data were questionnaire and interview. Questionnaire contained 14 questions was adopted from The Foreign Language Listening Anxiety Scale (FLLAS) developed by Kim (2000) that was given to the students and interview was conducted with an English teacher and three students. The results of this study indicate that there are several factors that cause listening anxiety. The first, the students feel confused and anxious because they are unable to catch the words conveyed by the speaker. The second, the students feel difficult to understand the pronunciation of the speaker. The third, the students feel afraid when the speaker conveying information too quickly. The fourth, the students feel worried about the limited time in doing the listening task. The fifth, the students feel anxious because they think the other student more understand about the contents of the English recording. And the last, the students feel nervous when they do not understand the meaning of each word because they are lack of vocabulary in English. In conclusion, the students feel anxious in doing the listening task which resulted in their listening skills getting lower when learning English in the classroom